2020
DOI: 10.3390/ani10020359
|View full text |Cite
|
Sign up to set email alerts
|

Running Head: Heat Affects Cholesterol and Bile Acid Alterations in Cholesterol and Bile Acids Metabolism in Large White Pigs during Short-Term Heat Exposure

Abstract: Heat stress influences lipid metabolism independently of nutrient intake. It is not well understood how cholesterol and bile acid (BA) metabolism are affected by heat stress. To investigate the alterations of cholesterol and bile acids when pigs are exposed to short term heat stress, 24 Large White pigs (63.2 ± 9.5 kg body weight, BW) were distributed into one of three environmental treatments: control conditions (CON, 23 °C with ad libitum intake; n = 8), heat stress conditions (HS, 33 °C with ad libitum inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
7
1
Order By: Relevance
“…Performance responses of pigs in response to treatment have been previously described in detail ( Fang et al., 2020 ). Briefly, pigs in the HS treatment had approximately 55% lower cumulative feed intake and lost body weight (−0.69 kg, P < 0.01) whereas TN and PF pigs gained 2.46 and 0.38 kg in body weight, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Performance responses of pigs in response to treatment have been previously described in detail ( Fang et al., 2020 ). Briefly, pigs in the HS treatment had approximately 55% lower cumulative feed intake and lost body weight (−0.69 kg, P < 0.01) whereas TN and PF pigs gained 2.46 and 0.38 kg in body weight, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed description of the methods has been previously published ( Fang et al., 2020 ). Briefly, 24 crossbred boars (63.2 ± 9.5 kg body weight) were randomly assigned to 1 of 3 groups: 1) thermoneutral conditions (TN, 23 ± 1 °C) ( n = 8), 2) exposed to heat stress conditions (HS, 33 ± 1 °C) ( n = 8), 3) pair-fed (PF, 23 ± 1 °C) ( n = 8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synergistic effect of BS and LTN could be attributed to the improvement of absorption and metabolism of fat and fat soluble components, such as LTN, whereas, BS has an amphipathic characteristic and is capable of transforming lipid bilayers to mixed micelles and facilitates the hydrolysis process induced by lipases [ 71 , 72 , 73 ]. Accordingly, the determination of carotenoid content in the present study showed the highest accumulation in the BS+LTN supplemented group ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The validity of respiratory rate as an indicator has been proven by several authors [ 45 , 70 , 83 , 105 , 106 ], who have used it as a thermal status indicator (see the Results section). In terms of reliability as an indicator, the current method with which this variable is measured has limitations, as counting the movements of the flank requires a trained observer.…”
Section: Discussionmentioning
confidence: 93%